Kombinasi Iradiasi dan Coating Kitosan untuk Pengendalian Cendawan Thielaviopsis paradoxa pada Buah Salak Selama Penyimpanan - Sri Lestari; Usman Ahmad; Evi Savitri Iriani; Fajar Kurniawan (Jurnal Keteknikan Pertanian, 2020)
Snake fruit is one of the export potential fruit which is susceptible to fungus. The objectives of this study are to analyze the effect of irradiation and chitosan coating on snake fruit damage caused by Thielaviopsis paradoxa and to determine the best treatment that can be used to control T. paradoxa fungus attack on snake fruit during storage. The treatments consist of 3 types: (1) irradiation (0.5 kGy; 1 kGy; 1.5 kGy), (2) coating followed by irradiation (0.5 kGy;1 kGy;1.5 kGy), (3) control (no treatment). The samples are stored at 12 oC (RH 70-75%). The results shows that the chitosan irradiation and coating treatment was proven to inhibit the growth of T. paradoxa fungus during storage. The best treatment is the the treatment with use 1 kGy irradiation dose which is combined with chitosan coating. The fruit damage for 20 days of storage is 41.67% with the severity of the disease is 21.67%. In application, the technology can effectively be applied considering the fungus attack on fruit is not as heavily as that in research. Irradiation dose of 1.5 kGy causes the flesh to mature.